"You're Really Just a Gay Man in a Woman's Body!": The Possibilities and Perils of Queer Sexuality. (June 2017) - Stone, Amy L.; Shapiro, Eve
Queer theory has long argued for the liberatory potential of separating masculinity from men. This article examines whether and how masculinities can be radically transgressive for individuals and simultaneously re-create gendered systems of inequality. In two case studies—a drag troupe and a queer leather club—we find that the cultivated queer sexualities were mimetic iterations of sexual practices among gay men and came rife with both the possibilities and problematics of these real and imagined tropes. We trace the consequences of this in two processes: the eroticization and self-exploration of masculinity and the reliance on validation from gay men. We find that the empowering sexualities taken up by individuals were concurrently rooted in and reproduced sexist meanings of desire and sexual agency. In so doing, we contribute to sociological understanding of masculinities by charting how androcentrism is reproduced in some groups, with or without the presence of male bodies.